2015
DOI: 10.1002/bit.25556
|View full text |Cite
|
Sign up to set email alerts
|

Random mutagenesis of amelogenin for engineering protein nanoparticles

Abstract: Nanoparticles made from recombinant proteins offer excellent potential for several nanotechnological applications. However, only a very limited number of proteins are currently being used for such purposes due to limited availability and stability. Therefore, we have investigated the enamel matrix protein amelogenin as a new alternative protein for use as recombinant nanoparticles. Amelogenin is a robust protein that has the ability to self-assemble into nanosized particles termed nanospheres. This self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…C. The pH solubility profile of rh174 exhibited a U‐shape with the lowest solubility close to pH 6.5, as in previous reports . A similar profile was observed for rh174CDB, but the fusion protein displayed a low solubility over a wider pH range.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…C. The pH solubility profile of rh174 exhibited a U‐shape with the lowest solubility close to pH 6.5, as in previous reports . A similar profile was observed for rh174CDB, but the fusion protein displayed a low solubility over a wider pH range.…”
Section: Resultssupporting
confidence: 82%
“…This has also recently been shown by others . Besides amelogenin fusion proteins, we have also reported that a random mutation amelogenin library can be used to create amelogenins with distinct solubility behavior, further demonstrating the possibilities to engineer the properties of this protein.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…It has been previously shown that the C-terminus has been associated with HAP binding. In an attempt to induce mineralization of amelogenin nanoribbons, we modified its C-terminus by extending it with a triple repeat of amelogenin sequence KTKR 47 48 , and tested the effect of additional electrostatic charges on self-assembly and mineralization. The resulting rH174-(+9) protein was exposed to the same self-assembly protocol as described above and also assembled into ribbons that were organized in a parallel fashion, but with extremely regular distances of about 69 nm between ribbons when immobilized on glass surfaces ( Fig.…”
Section: Resultsmentioning
confidence: 99%